Structure of glycosylated NPC1 luminal domain C reveals insights into NPC2 and Ebola virus interactions. - Zhao, Y; Ren, J; Harlos, K; Stuart, D (Wiley, 2016)
Niemann-pick type C1 (NPC1) is an endo/lysosomal membrane protein involved in intracellular cholesterol trafficking, and its luminal domain C is an essential endosomal receptor for Ebola and Marburg viruses. We have determined the crystal structure of glycosylated NPC1 luminal domain C and find all seven possible sites are glycosylated. Mapping the disease mutations onto the glycosylated structure reveals a potential binding face for NPC2. Knowledge-based docking of NPC1 onto Ebola viral glycoprotein and sequence analysis of filovirus susceptible and refractory species reveals four critical residues, H418, Q421, F502 and F504, some or all of which are likely responsible for the species-specific susceptibility to the virus infection.